Expanding the Maine Economy - McKernan, John (Maine Policy Review, 1994)
Maine Governor John McKernan highlights his administration’s efforts to expand the state’s economy, including its initiatives to reduce the cost of doing business in the state, to reform education, and to build consensus among various constituencies around goals and strategies for economic development. The article is based on McKernan’s remarks at the 21st annual Governor’s Economic Development Conference held at the University of Maine last fall.